Use of Instagram as an Educational Tool with Pre-Service Teachers and the Impact on Digital Competence in Communication and Collaboration - José Antonio Martínez-Domingo; Inmaculada Aznar-Díaz; José María Romero-Rodríguez; Juan José Victoria-Maldonado (Education Sciences)
The rise of social media is transforming education by replacing traditional materials and promoting digital competence, a key area of focus in current training. Platforms like Instagram facilitate collaboration, access to learning, and content creation, becoming essential tools for the development of students and future educators in digital environments. This study aimed to enhance the digital competence of pre-service teachers, particularly in communication and collaboration, through Instagram as an educational tool. A quasi-experimental study with pretest and post-test measures was conducted, involving 391 students from the University of Granada. The results indicated an intermediate level of digital competence with improvements in both groups, though no significant differences were found between them. However, significant effects were observed in the intragroup analysis. The experimental group, which used Instagram as an educational tool for 11 weeks, showed improvements in communication and collaboration, digital content creation, and security. The control group also demonstrated progress, mainly in information search and problem-solving. These improvements align with previous studies, though the progress in the control group may be attributed to factors such as content focused on educational technology, student motivation, and engagement. This study confirms that social media can enhance digital competence as a learning tool.